From Civil Religion to Presidential Public Theology—A Re-evaluation of the American Civil Religion Phenomenon. The Case of George H. W. Bush - Lejon, Kjell O. (European Journal of Multidisciplinary Studies, 2018)
Since the inauguration of the civil religion debate in the United States in 1967, it has been argued that the religious dimension of American presidency should be understood as a kind of civil religion, normally based upon the definition of Jean Jacque Rousseau, or variations of this his definition. However, in this article the author argues, based upon the empirical material presented in Public Papers of the President and elsewhere, that a more accurate description of the religion dimension of some modern presidencies is public theology. He uses the presidency of George H. W. Bush as a case study.
Keywords: Civil religion, Public Theology, American presidents, Robert N. Bellah, George H. W. Bush